2018
DOI: 10.1016/j.chiabu.2017.10.011
|View full text |Cite
|
Sign up to set email alerts
|

Children’s disclosures of sexual abuse in a population-based sample

Abstract: Most previous studies on disclosing child sexual abuse (CSA) have either been retrospective or focused on children who already have disclosed. The present study aimed to explore the overall CSA disclosure rate and factors associated with disclosing to adults in a large population-based sample. A representative sample of 11,364 sixth and ninth graders participated in the Finnish Child Victim Survey concerning experiences of violence, including CSA. CSA was defined as having sexual experiences with a person at l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
52
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(68 citation statements)
references
References 36 publications
13
52
0
2
Order By: Relevance
“…It is complicated to estimate the extent of the under-reporting of CSA. However, a recent study estimated that approximately 20% of CSA victims do not disclose the event to anyone [4]. In this study, the question whether cases reported to someone reached the authorities remained unanswered, as 48% of the disclosures were to friends, and only 12% were disclosures directly to authorities.…”
Section: Abuse In Mock Evaluationsmentioning
confidence: 79%
See 1 more Smart Citation
“…It is complicated to estimate the extent of the under-reporting of CSA. However, a recent study estimated that approximately 20% of CSA victims do not disclose the event to anyone [4]. In this study, the question whether cases reported to someone reached the authorities remained unanswered, as 48% of the disclosures were to friends, and only 12% were disclosures directly to authorities.…”
Section: Abuse In Mock Evaluationsmentioning
confidence: 79%
“…However, Melkman, Hershkowitz and Zur [3] estimated that about 58% of disclosures made by the alleged victims could be considered credible. Comparable results have been reached by 4 Korkman, Antfolk, Fagerlund, and Santtila [5], who report that 25-40% of CSA allegations in Finland might be unfounded. Panel A shows a base rate of .03 and no other observation has been made yet.…”
Section: Abuse In Mock Evaluationsmentioning
confidence: 82%
“…There may be several reasons why youths who have been exposed to trauma are not identified in youth mental health clinics. For instance, children with sexual abuse experiences often do not disclose their abuse, 10 and therapists may not link children’s problems to trauma if the therapists do not ask about abuse. This is alarming, since an increase in time from incident to disclosure among adult female survivors of childhood sexual abuse has been found to be significantly associated with an increase in symptoms of posttraumatic stress, anxiety, and depression, 11 underscoring the importance of early detection.…”
Section: Introductionmentioning
confidence: 99%
“…However, only 7% had reported it to the police, 5% to a teacher, 4% to a social worker, 3% to the school counselor and 2% to the school nurse. The main justification for not revealing it was to consider the experience as irrelevant (41%) 18 .…”
Section: Discussionmentioning
confidence: 99%